Functional Plasticity of the AgrC Receptor Histidine Kinase Required for Staphylococcal Virulence. Issue 1 (19th January 2017) - Wang, Boyuan; Zhao, Aishan; Xie, Qian; Olinares, Paul Dominic; Chait, Brian T.; Novick, Richard P.; Muir, Tom W.
Summary: Staphylococcus aureus employs the receptor histidine kinase (RHK), AgrC, to detect quorum-sensing (QS) pheromones, the autoinducer peptides (AIPs), which regulate the virulence of the bacterium. Variation in the QS circuit divides S. aureus into four subgroups, each producing a specific AIP-AgrC pair. While the timing of QS induction is known to differ among these subgroups, the molecular basis of this phenomenon is unknown. Here, we report the successful reconstitution of several AgrC variants and show that the agonist-induced activity of the receptors varies in a manner that accounts for these temporal differences in QS induction. Our studies also reveal a key regulatory hotspot on AgrC that controls the basal activity of RHK as well as the responsiveness of the system to ligand inputs. Collectively, these studies offer insights into the capacity of the RHK for adaptive evolution. Graphical Abstract: Highlights: AgrC activity correlates with the timing of agr induction among S. aureus subgroups Single mutations in AgrC produce constitutive mutants by modifying the response curve AgrC constitutive mutants differ in phospho-transfer rate with non-cognate AIP bound Abstract : Sequence variants of AgrC, a receptor histidine kinase involved in virulence regulation in S. aureus, show different activity depending on the conformational output of the sensor domain. Single mutations in AgrC generate constitutive mutants through modification of the response curve, and these mutants phosphorylate AgrA at different rates in the presence of inhibitors, revealing a key regulatory hot spot.